Choosing a price and cost combination: The role of correlation - Avner Bar-Ilan; Yishay Maoz (Journal of Risk and Financial Management, 2021)
Often, firms can choose from different combinations of price and cost processes. For example, they can choose between different production locations or technologies, between different products to produce, or between different locations for selling them. To study the choice of the optimal combination, we return to themodel that was developed by Dixit and Pindyck, where both output price and production cost are stochastic processes, and add a novel focus on how the correlation between these processes affects the firm's decision. We find that, ceteris paribus, the firm prefers the combination with the lowest correlation between the processes, as it seeks a greater profitability variance which maximizes its value.
Keywords: C61; D40; 330; investment; real-options; correlation